(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The communicative dimension of corporate social responsibility has been identified as a ‘double edged sword’ for companies. Although prior literature recognises the value of communication in CSR implementation, there are also established complexities in how to make CSR actions known and recognised by stakeholders. This study explores the seeming challenges encountered by a multinational CSR frontrunner in Ghana in communicating social responsibility activities to its stakeholders. The qualitative study focused on semi-structured interviews with CSR communication managers and other key stakeholders in the company who have in-depth knowledge about CSR. The empirical results demonstrate that unique contextual conditions are major sources of complexities and tensions in CSR communication. Findings revealed key CSR communication challenges including cost of communicating CSR, ‘cash cow’ perceptions of multinational companies, high stakeholder expectations and demands for CSR initiatives, and intransigent media landscape. The literature suggests that there is sparse research that examines specific challenges in communicating corporate responsibility. The study therefore advances the CSR communication scholarship by providing insights into unique challenges faced by multinational companies in host countries, particularly within a sub-Saharan African context, Ghana, along with the strategies adopted to overcome the challenges. Being cognisance of how cultural diversity and local situations influence communications about CSR can provide both theoretical and practical implications for researchers and practitioners.